2012
DOI: 10.1292/jvms.12-0107
|View full text |Cite
|
Sign up to set email alerts
|

FDG Uptake of Normal Canine Brain Assessed by High-Resolution Research Tomography-Positron Emission Tomography and 7 T-Magnetic Resonance Imaging

Abstract: ABSTRACT. The purpose of this study was to assess the normal distribution of 18 F-fluoro-2-deoxy-D-glucose (FDG) uptake of canine brain structures using a high-resolution research tomography-positron emission tomography (HRRT-PET) and 7 T-magnetic resonance imaging (MRI) fusion system. FDG-PET and T2-weighted MRI of the brain were performed on 4 healthy laboratory beagle dogs. On MRI, regions of interests (ROIs) were manually drawn over 51 intracranial structures, including nine gross structures and 42 detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
12
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 27 publications
9
12
1
Order By: Relevance
“…Additionally, the aforementioned study used a different anesthetic protocol, and anesthetic protocols have been shown to affect SUV values . A recent study specified SUV values for numerous detailed brain structures . The distribution of SUV values (i.e., the highest and the lowest glucose uptake pattern) was similar to that in our study.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Additionally, the aforementioned study used a different anesthetic protocol, and anesthetic protocols have been shown to affect SUV values . A recent study specified SUV values for numerous detailed brain structures . The distribution of SUV values (i.e., the highest and the lowest glucose uptake pattern) was similar to that in our study.…”
Section: Discussionsupporting
confidence: 77%
“…The distribution of SUV values (i.e., the highest and the lowest glucose uptake pattern) was similar to that in our study. In the previous study, they detected the highest glucose uptake in the caudal colliculi, followed in order by the cerebellar vermis and the caudate nuclei . In our study, the highest glucose uptake was also detected in the caudal colliculi, followed by the caudate nuclei and the cerebellar vermis (the latter only in adult dogs).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, CT has a number of shortcomings in soft tissue imaging; therefore, MRI can be utilised for precise anatomical localisation of malignant lesions as an alternative to CT (Cho et al 2008). Clinical application of PET/CT has been reported in a number of dogs with spontaneously occurring tumours , whereas use of PET/MRI in canines is limited to the healthy or epileptic brain, intracranial HS and pituitary microtumours (Kang et al 2009;Kang et al 2012;Jokinen et al 2014;Son et al 2015). In the present case, 7 T-MRI clearly visualised the cerebellar and thyroid lesions, thus helping in the identification of the anatomical location of the hypermetabolic lesions on PET.…”
Section: Discussionmentioning
confidence: 99%